Size and stability of curcumin niosomes from combinations of Tween 80 and Span 80 - Masrina Mohd Nadzir; Tan, Wei Fen; Abdul Rahman Mohamed; Siti Farhana Hisham (Penerbit Universiti Kebangsaan Malaysia, 2017)
The ratios of Tween 80 to Span 80 are important in controlling the physicochemical characteristics of curcumin niosomes. Thus, in this study the correlations of combination of Tween 80 and Span 80 at different ratios with the size and stability of curcumin niosomes were investigated. Initially curcumin was dissolved in chloroform and methanol (v/v= 3:1), followed by the preparation of niosomes by thin-film hydration method with the mole ratio of mixture of Tween 80 and Span 80 to cholesterol of 2:1. The ratios of Tween 80 to Span 80 in the mixture were set at 1:1, 1:9, 9:1, 2:3 and 3:2 with Hydrophilic-Lipophilic Balance (HLB) values of 9.65, 5.37, 13.93, 8.58 and 10.72, respectively. As expected, niosome barely formed at HLB value 13.93. This might be due to the molecule being hydrophilic and well hydrated which inhibits the formation of a stable bilayer in solution. It was found that the formulation which has higher Span 80 and lower HLB value leads to larger niosome before sonication. The largest niosome size achieved from Tween 80 to Span 80 ratio of 1:9 and 2:3 was 77.36 and 59.85 μm, respectively. On the other hand, for the ratio of 3:2, the largest niosome formed before sonication was less than 50.00 μm. After sonication, the niosome size reduced to less than 35.00 μm for all formulations. It was showed that formulation with Tween 80 to Span 80 ratio of 1:9 has superior curcumin entrapment efficiency and best stability during storage. The results demonstrated that appropriate ratio of Tween 80 to Span 80 was necessary for forming small and stable curcumin niosomes.